The Retreats of Reconstruction : Race, Leisure, and the Politics of Segregation at the New Jersey Shore, 1865-1920 - Goldberg, David E. (Book collections on Project MUSE., 2016)
This book examines how de facto segregation unfolded and operated at the New Jersey shore after the Civil War. Weaving together histories of race, leisure, and consumption, it argues that the politics of mass consumption contained early desegregation efforts and prolonged Jim Crow.